2020
DOI: 10.21203/rs.3.rs-32099/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A designathon to co-create community-driven HIV self-testing services for Nigerian youth: findings from a participatory event

Abstract: Background: Youth are at high risk for HIV, but are often left out of designing interventions, including those focused on adolescents. We organized a designathon for Nigerian youth to develop HIV self-testing (HIVST) strategies for potential implementation in their local communities. A designathon is a problem-focused event where participants work together over a short period to create and present solutions to a judging panel.Methods: We organized a 72-hour designathon for youth (14-24 years old) in Nigeria to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…We found that the youth teams were able to develop solutions that were highly ranked among independent external reviewers. These findings are consistent with previous designathons where high-quality proposals and ideas emerged at the end of the event [ 30 ]. However, designathons and similar events may not have ideas translated into programs or research studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that the youth teams were able to develop solutions that were highly ranked among independent external reviewers. These findings are consistent with previous designathons where high-quality proposals and ideas emerged at the end of the event [ 30 ]. However, designathons and similar events may not have ideas translated into programs or research studies.…”
Section: Discussionsupporting
confidence: 92%
“…Students from a wide range of academic backgrounds, age groups, and disciplines played a pivotal role in the designathon activities. This is consistent with other designathon literature that has successfully engaged a diverse group of students to create innovative health solutions [ 30 , 31 ]. This finding also suggests that schools and universities may be a key partner for institutionalizing designathons within some communities.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations